Malay Version of Acceptance and Action Questionnaire-II (AAQ-II): A Reliability and Validity Analysis in Non-Clinical Samples - Mohd Bahar, Farhana Harzila; Mohd Kassim, Mohd Amiruddin; Pang, Nicholas Tze Ping; Koh, Eugene Boon Yau; Kamu, Assis; Ho, Chong Mun (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Majority of gestational diabetes mellitus (GDM) mothers resume normal glycaemic state after delivery. However, this hyperglycaemic condition may persist in some women. Postpartum GDM mothers have a higher risk of progression to diabetes and prediabetes than those with normal pregnancy. This study was aimed to determine the prevalence of prediabetes among postpartum GDM mothers and its associated factors during six weeks of postpartum glucose testing. MATERIALS AND METHOD: A cross-sectional secondary data review was conducted from January 2021 until May 2021 among postpartum mothers with history of GDM who performed postpartum glucose testing in all government health clinics in Besut, Terengganu from January 2018 until December 2019. A descriptive and multiple logistic regression analysis were performed using IBM SPSS Statistics version 26 software. RESULT: A total of 429 cases were included. Prevalence of diabetes and prediabetes was 2.3% (95% CI 1.6%, 3.0%) and 13.8% (95% CI 12.1%, 15.5%), respectively. There was significant associations found between previous history of GDM (Adj. OR 3.28; 95% CI 1.83, 5.87; p < 0.001) and insulin usage (Adj. OR 2.75; 95% CI 1.51, 4.99; p= 0.001) with development of prediabetes at postpartum period. CONCLUSION: The prevalence of diabetes and prediabetes among postpartum GDM mothers in Besut district was as high as other studies in Malaysia and globally. Women with a previous history of GDM and insulin usage should be focused on prevention strategies as they were at higher risk of developing prediabetes in the postpartum period.